Financial Literacy and Electronic Money Empower Online Drivers' Impact Globally: Literasi Keuangan dan Uang Elektronik Memberdayakan Dampak Pengemudi Online Secara Global - Zainudin , Achmad; Rahayu, Ruci Arizanda (Indonesian Journal of Law and Economics Review, 2024)
This study investigates how financial literacy, self-control, and electronic money influence the lifestyle of online motorcycle taxi drivers in Sidoarjo, using quantitative methods and a sample size of 96 respondents. Through questionnaires and data analysis including validity tests, reliability tests, multiple linear regression analysis, and t-tests using SPSS version 26, the research finds a significant positive impact of these factors on drivers' lifestyles. The findings underscore the importance of promoting financial literacy and self-control among drivers, with implications for industry stakeholders and policymakers aiming to enhance driver well-being and sustainability in the online motorcycle taxi sector. Highlight: Financial literacy and self-control impact drivers' lifestyles significantly. Electronic money improves efficiency and security in financial transactions. Promoting literacy and control sustains well-being and industry growth. Keyword: Financial Literacy, Self-Control, Electronic Money, Online Motorcycle Taxi Drivers, Sidoarjo